Grammatical Semantics in Limerick A Collection of Indonesian Proverb and Pantun by the Brilliant Editorial Team - Febri Yanti; Abdul Malik; Tety Kurmalasari (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
This study discusses grammatical semantics seen from the types of context in the contextual meaning contained in the oral literary works of Limerick in the book Collection of Indonesian Proverbs and Pantun by the Cemerlang Editorial Team. This research method is descriptive using a qualitative approach. Data collection techniques used are documentation, observe and record. Data analysis techniques in this study used descriptive qualitative analysis techniques. The results of the analysis of the data obtained from the limerick in the book Collection of Indonesian Proverbs and Pantun by the Cemerlang Editorial Team in terms of the types of context in contextual meaning are the context of purpose, the context of the speaker's or listener's mood and the context of the object.